(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة توزع 15 مركباً من مركبات ثنائي فينيل متعدد الكلور (PCBs) في عينات مائية ورسوبية جمعت فصلياً من أربع مواقع مختلفة من شاطئ مدينة اللاذقية خلال الفترة الممتدة من تشرين الثاني 2009 حتى آب 2010 و درست بتقنية الكروماتوغرافيا الغازية. تراوحت التراكيز الإجمالية لمركبات الـ PCBsفي العينات المائية بين 2.84 ng/l و 13.48 ng/l. تأثر تركيز مركبات الـ PCBs في العينات المائية بطبيعة المناطق المدروسة والتغيرات الفصلية وبمصادر التلوث لكل موقع, حيث تميزت منطقة البحوث البحرية بتراكيز منخفضة بالمقارنة مع المناطق الأخرى خصوصاً في فصلي الخريف والشتاء. تراوح التركيز الإجمالي لمركبات الـ PCBs في العينات الرسوبية بين 7.09 ng/l و 23.01 ng/l. أظهرت النتائج انخفاض تركيز لمركبات الـ PCBs في العينات الرسوبية في فترتي الخريف والشتاء بفعل الأمواج البحرية والحركة الدورانية من الأسفل إلى الأعلى والتي تعيد تعليق المواد الملوثة من الرسوبيات السطحية إلى العمود المائي. بينت الدراسة أيضاً أن المماكبات الثقيلة هي الأكثر توزعاً في الرسوبيات وبشكل خاص مركبات سداسي وسباعي كلور ثنائي فينيل كونها مقاومة لعمليات التحلل. كما أوضحت النتائج وجود علاقة ارتباط مباشرة بين ΣPCBs المتراكمة في الرسوبيات ومحتوى الرسوبيات من المادة العضوية. The distribution of 15 polychlorinated biphenyl compounds (PCBs) in water and sediment samples was studied. These samples were collected quarterly from four different coastal regions of Lattakia during period ranged from November 2009 until August 2010, and studied by using gas chromatography technique. The total concentrations of PCBs in the water samples ranged between 2.84 ng/l and 13.48 ng/l. These concentrations were affected by the nature of the studied areas, seasonal changes and sources of pollution for each site. Marine Research region was characterized by lower concentrations in comparison with other regions, especially in the autumn and winter. In the sediment samples, the total concentration of PCBs ranged between 7.09 ng/l and 23.01ng/l. The results showed low concentration of PCBs in the sediment samples during Autumn and Winter periods, due to sea waves and to the rotational movement from the bottom up to the top, which re-distribute contaminants from sediment surface to the water column. This study also showed that the heavy congeners of PCBs are the most widely distributed in the sediment especially heptachlor and hexachlor biphenyl. The results revealed direct correlation between ∑PCBs accumulated in the sediment, and sediment content of organic matter